EXTENSIVE READING AND ITS CONTRIBUTION TO VOCABULARY GROWTH IN EFL LEARNERS - Risma Kartika Dewi; Rinda Riztya; Sofia F Rahmani (Adisam Publisher, 2026)
This study aims to examine the contribution of extensive reading to vocabulary growth in English as a Foreign Language (EFL) learners through a literature review approach. The method used was a literature review, reviewing various relevant scientific articles, books, and research reports related to extensive reading practices and vocabulary acquisition. The results of the study indicate that extensive reading has a significant impact on increasing the number and quality of learners' vocabulary, primarily through repeated exposure to words in meaningful contexts. Furthermore, reading activities that are independent, enjoyable, and appropriate to the learner's ability level have been shown to increase learning motivation and strengthen long-term vocabulary retention. Factors such as selecting appropriate reading materials, reading frequency, and a supportive learning environment also play important roles in optimizing learning outcomes. Thus, extensive reading can be an effective strategy for vocabulary development for EFL learners when implemented consistently and in a structured manner.